Development and Investigation of a Steel–Molybdenum Coating Deposited by the Gas–Thermal Method - Bolshakov, V.I.; Hlushkova, D.B.; Kalinin, O.V.; Voronkov, O.I.; Kostina, L.L. (Металлофизика и новейшие технологии, 2019)
The steel–molybdenum coating applied to the piston rings group made of high-strength cast iron provides a good conformability, low wear rate, and low coefficient of friction. This fact is explained by the specific characteristics of molybdenum oxides. Сталь-молибденовое покрытие, нанесённое на поршневые кольца из высокопрочного чугуна, обеспечивает хорошую прирабатываемость, малую интенсивность износа, низкий коэффициент трения. Этот факт объясняется специфическими свойствами оксидов молибдена. Сталь-молібденове покриття, що нанесено на поршневі кільця з високоміцного чавуну, забезпечує добру припрацьовуваність, малу інтенсивність зношування, низький коефіцієнт тертя. Цей факт пояснюється специфічними властивостями окислів молібдену.